Experimental and theoretical study of the adsorption of mixed low carbon alcohols and acids from Fischer Tropsch synthesis wastewater by activated carbon. (1st May 2023) - Zhang, Yingying; Dou, Baojuan; Liu, Xiao; Fan, Honglei; Geng, Chunyu; Liu, Xingchen; Chang, Jie; Hao, Qinglan; Hu, Xin; Yang, Yong; Li, Yongwang; Teng, Botao
Graphical abstract: C1-2 alcohols and acetic acid adsorption capacity depend on the ultra-micropore (<0.9 nm); pentanol adsorption is mainly determined by the surface area; while the adsorption capacities of C3-4 alcohols and acids are attributed to the synergetic effects of the micropore and surface area. Highlights: Adsorption capacities of C1-2 alcohols and acids depend on the ultra-micropore. Adsorption capacity of pentanol is mainly determined by the surface area. Adsorption capacities of C3-4 alcohols and acids depends on micropore and surface area. This work sheds light into the adsorption of low-carbon alcohols and acids. Abstract: To purify and recycle the low-carbon alcohols and acids in wastewater by a green method with high efficiency is of great significance in chemical engineering process, such as indirect coal liquefaction (Fischer Tropsch Synthesis, FTS), which produces a large amount of alcohol and acid-containing wastewater. Adsorption-desorption of low-carbon alcohols and acids in wastewater by activated carbon is a promising method for industrial application. The adsorption capacity of low-carbon alcohols and acids in activated carbons is closely related with their pore and surface properties. However, this was seldom studied due to the complex properties of carbon materials with different pore size, distribution and volume, as well as surface area and hydrophobicity. In this work, four commercial activated carbon materials (AC1 ∼ 4) with similar hydrophobicity and different pore and surface structure were chosen to explore the possible correlation of the adsorption capacity of C1-5 alcohols, C2-4 acids and FTS modeling wastewater. The batch method was used to investigate the adsorption capacity of AC1 ∼ 4 on low-carbon alcohols and acids as well as FTS modeling wastewater; while density functional theory (DFT) calculation was performed to investigate the adsorption energies of low-carbon alcohols and acids in carbon nanotubes with different pore sizes. Both the experimental and theoretical results indicate that the adsorption capacities of methanol, ethanol and acetic acid are strongly dependent on the ultra-micropores (<0.9 nm) due to their small molecular weight; and the adsorption capacity of pentanol is mainly determined by the surface areas due to its relatively high molecular weight and low polarity; while the adsorption capacities of C3-C4 alcohols and acids are well correlated with the microporous volume and surface area. In addition, and the adsorption capacities of acids were also related with the content of surface COOH species. AC2 has the highest adsorption capacity of mixed low-carbon alcohols and acids (196.2 mg/g) in FTS modeling wastewater due to its abundant ultra-micropore and high specific surface area. This work sheds light into the development of adsorbents with high adsorption capacity of low-carbon alcohols and acids, and provides solid experimental and theoretical support in the further purification of FTS wastewater and recovery of valuable chemicals.